Sustainability and Corporate Reporting using ERP Systems: Challenges and Opportunities for the Accounting and Auditing Profession - Laura-Eugenia-Lavinia BARNA; Bogdan-Stefan IONESCU; Liliana IONESCU-FELEAGA (Audit Financiar, 2024)
As a result of the massive digitalization of recent years, ERP systems have started to play an important role in the life cycle of an organization, raising a number of challenges and opportunities especially for the accounting and auditing profession. The accounting and the auditing professions represent two very versatile professions as a result of the changes that have taken place from the moment of their appearance until now, they are constantly improving with the evolution of digitalization. Digitalization has led to the development of accounting and auditing organizations and of course to the focus of attention on sustainability processes and how their corporate reporting is done. The many advantages that ERP systems offer to professional accountants and auditors, as well as other categories of users, have influenced many organizations to resort to the implementation of these systems. Thus, to highlight the main challenges and opportunities that ERP systems offer to the accounting and auditing profession from the perspective of how to ensure sustainability and corporate reporting, the authors performed a quantitative bibliometric analysis, selecting a sample of Web of Science cited articles. The results indicated that ERP systems have a major impact on the decisions adopted by organizations, more specifically they ensure a true picture of the organization's situation, having a significant influence on the way of corporate reporting and on sustainability.